2003
DOI: 10.1002/ajmg.a.10104
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal detection of rare chromosomal autosomal abnormalities in Europe

Abstract: The aim of the present study was to evaluate the prenatal detection of rare chromosomal autosomal abnormalities by ultrasound (US) examination. Data were obtained from 19 congenital malformation registries from 11 European countries, between 01/07/96 and 31/12/98. A total of 664,340 births were covered and 7,758 cases with congenital malformations were recorded. Rare autosomal abnormalities were diagnosed in 114 cases (6.6%) from a total of 1,738 chromosome abnormalities. There were a wide variety of autosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
6
14
4
Order By: Relevance
“…With the advent of prenatal screening in the first trimester, many fetuses that would have miscarried or been stillborn are diagnosed with a chromosome error. Our rate of 43.6/10 000 births, for all chromosome abnormalities, is therefore, as expected, higher than that found in newborn studies 3,[15][16][17] where rates of 17-31/10 000 were found.…”
Section: Discussionsupporting
confidence: 55%
“…With the advent of prenatal screening in the first trimester, many fetuses that would have miscarried or been stillborn are diagnosed with a chromosome error. Our rate of 43.6/10 000 births, for all chromosome abnormalities, is therefore, as expected, higher than that found in newborn studies 3,[15][16][17] where rates of 17-31/10 000 were found.…”
Section: Discussionsupporting
confidence: 55%
“…After excluding those abnormalities considered to be lethal in utero, the rate of additional rare trisomies and unbalanced rearrangements is less than 1/1000, a rate that is consistent with the livebirth data. Approximately a half of the rare autosomal chromosomal abnormalities seen in the second trimester can be expected to show abnormal ultrasound findings (33). Chromosome abnormalities are much more frequently encountered in CVS specimens (Table 1 and Fig.…”
Section: Cytogenetically Recognizable Imbalancesmentioning
confidence: 99%
“…Abnormal prenatal ultrasound findings in these fetuses were very heterogeneous. They include duodenal atresia and annular pancreas (Fernandez-Gonzalez et al, 2001), increased nuchal thickness (McClelland et al, 1998), unilateral duplex renal system with pyelectasis (Chen et al, 2001), cleft lip and palate (Chen et al, 2001), hypoplastic left heart (Baena et al, 2003), diaphragmatic hernia (Baena et al, 2003), short femura and humeri, and overlapping of the toes (Chen et al, 2004). Moderate ventriculomegaly and minor growth retardation were the only abnormalities observed in our case.…”
Section: Discussionmentioning
confidence: 99%